Cannabidiol Attenuates Experimental Autoimmune Encephalomyelitis Model of Multiple Sclerosis Through Induction of Myeloid-Derived Suppressor Cells - Elliott, David M.; Singh, Narendra; Nagarkatti, Mitzi; Nagarkatti, Prakash S. (Frontiers in Immunology, 2018)
Multiple sclerosis (MS) is a chronic debilitating autoimmune disease without a cure. While the use of marijuana cannabinoids for MS has recently been approved in some countries, the precise mechanism of action leading to attenuate neuroinflammation is not clear. We used experimental autoimmune encephalomyelitis (EAE), a murine model of MS, to explore the anti-inflammatory properties of cannabidiol (CBD), a non-psychoactive cannabinoid. Treatment with CBD caused attenuation of EAE disease paradigms as indicated by a significant reduction in clinical scores of paralysis, decreased T cell infiltration in the central nervous system, and reduced levels of IL-17 and IFNγ. Interestingly, CBD treatment led to a profound increase in myeloid-derived suppressor cells (MDSCs) in EAE mice when compared to the vehicle-treated EAE controls. These MDSCs caused robust inhibition of MOG-induced proliferation of T cells in vitro. Moreover, adoptive transfer of CBD-induced MDSCs ameliorated EAE while MDSC depletion reversed the beneficial effects of CBD treatment, thereby conclusively demonstrating that MDSCs played a crucial role in CBD-mediated attenuation of EAE. Together, these studies demonstrate for the first time that CBD treatment may ameliorate EAE through induction of immunosuppressive MDSCs.